Pengaruh Pola Asuh Orang Tua Terhadap Pengembangan Karakter Peduli Sosial - Muhammad Husni; Arif Rahman Hakim; Nia Budi Harti; Aulia Dwi Hasani (Concept: Journal of Social Humanities and Education, 2023)
This study aims to determine whether there is an influence of parenting styles on the development of students' social concern character. The research was conducted in class VA with 21 student of SDN 1 Pengadangan as respondents in the academic year 2022/2023. The research method used is quantitative research with an ex-post facto research method. The results of the hypothesis test analysis conducted by the researcher indicate that there is an influence of parenting styles on the development of students' social concern character using the t-test formula, with the testing criteria being that if the tcount > ttable value at a significance level of 0.05 (5%), then there is an influence between variables X and Y. Based on the results of the hypothesis test calculation of the influence of parenting styles on the development of students' social concern character, with a tcount 12.143 > ttable 2.080 at a significance level of 0.05. Meanwhile, the significance value of the influence of parenting styles on the development of students' social concern character is 0.00 < 0.05 (5%). Therefore, it can be concluded that there is an influence of parenting styles on the development of fifth-grade students' social concern character.